Oral bisphosphonate use and age‐related macular degeneration: retrospective cohort and nested case–control study. Issue 1 (24th January 2018) - Garriga, Cesar; Pazianas, Michael; Hawley, Samuel; Delmestri, Antonella; Prieto‐Alhambra, Daniel; Cooper, Cyrus; Judge, Andrew
Abstract: Our objective here was to determine whether oral bisphosphonate (BP) use is associated with the incidence of age‐related macular degeneration (AMD). We performed a population‐based study using electronic health records from UK primary care (Clinical Practice Research Datalink). A cohort of 13, 974 hip fracture patients (1999–2013) was used to conduct (1) a propensity score–matched cohort analysis and (2) a nested case–control analysis. Hip fracture patients were aged ≥50 years without AMD diagnosis before hip fracture date or in the first year of follow‐up. Among 6208 matched patients and during 22, 142 person‐years of follow‐up, 57 (1.8%) and 42 (1.4%) AMD cases occurred in BP users and non‐BP users, respectively. The survival analysis model did not provide significant evidence of a higher risk of AMD in BP users (subhazard ratio: 1.60; 95% confidence interval (CI): 0.95–2.72; P = 0.08), although there was a significant increased risk among BP users with high medication possession ratio (MPR) (top quartile) relative to non‐BP users (odds ratio: 5.08, 95% CI: 3.11–8.30; P < 0.001, respectively). Overall, oral BP use was not associated with an increased risk of AMD in this cohort of hip fracture patients, although the risk increased significantly with higher MPR. More data are needed to confirm these findings.